(untitled) (Zaporizhzhia Historical Review, 2021)
The subject matter is the manifestation of polysemy as a language universal in the scientific and technical terminology (in French).The research objective of the research is to determine the causes of polysemic scientific and technical terms and to analyze their functioning in metallurgy, machine engineering, information science and electrical engineering. Terminological meanings of common polysemic words are formed either in the process of narrowing or specialization of notion, or in the process of metaforization. In some terminologies the transition of meaning on the basis of metonymy and synecdoche are observed.